AVTOTRANSPORT KORXONALARINI BOSHQARISHDA QAROR QABUL QILISH USULLARINI QO’LLASH - Islomov, Sh.E.; Asqarov, I.B. (SCIENCE and SOCIETY, 2022)
The article analyzes the factors affecting with equipment of the technical base of motor transport companies with technological equipment. To identify the main of these factors was used the method of expert evaluation.